Pre Calc

posted by .

How to prove tan4x = 1-8 sin squared of cos squared of x

  • Pre Calc -

    I don't think you really meant

    tan(4x) = 1 - sin^2(cos^2(x)), so do you mean

    tan 4x = 1 - 8 sin^2 x cos^2 x?

    Let's see.
    8sin^2 x cos^2 x = 2*sin^2(2x))
    tan(4x) =? 1 - 2sin^2(2x)

    Naah. Check your problem again.

    However, cos(4x) = 1 - 2sin^2(2x))

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calc

    Where do I start to prove this identity: sinx/cosx= 1-cos2x/sin2x please help!! Hint: Fractions are evil. Get rid of them. Well, cos2x = cos 2 x - sin 2 x, so 1-coscx = 1 - cos 2 x - sin 2 x = 1 - cos 2 x + sin 2 x You should be able …
  2. Mathematics

    I have to show that for any (pi)A, Sin(A)squared + Cos(A)squared = 1. I don't really get the question... am I supposed to multiply A by pi?
  3. math

    How do i find the area of a triangle? For example: A squared + b squared= c squared 8.5 squared + 6.4 squared= c squared 72.25 + 40.96= c squared 113.21=c squared 10.6400188=c even tho i thought this was the answer it is not because
  4. math

    i am having a minor difficulty i've been stuck for over an hour and don't know what to do i don't know is this right ?
  5. calculus

    prove cos squared B- sin squared B= 2cos squared B -1
  6. algebra 2 multiple choice HELP

    find f(a), if f(t) = 2t2(squared)-t-2 A. 2(a+t)2(squared)-2t+1-2 B. 2(t+a)2(squared)-2(t+a)-2 C. 2a2(squared)-a-2 D. 4a2(squared)-2a-2 I put (squared) because the two in front of it means it's being squared... please help. thanks!
  7. math

    prove the identity : cos^4 theta- sin ^4 thetaover sin squared theta cos squared theta =cot squared theta - tan squared theta
  8. Precalculus

    Prove or disprove cos(x+y)cos(x-y)=cos squared (x) - Sin squared (x) I dstributed the cosines and attempted to cancel out terms but I can't get the signs right. Any help on what I am missing?
  9. Precalculus with Trigonometry

    Prove or disprove the following Identities: cos(-x) - sin(-x) = cos(x) + sin (x) sin raised to the 4 (theta) - cos raised to the 4 (theta) = sin squared (theta) - cos squared (theta) cos (x+(pi)/(6)) + sin (x - (pi)/(3)) = 0 cos(x+y)cos(x-y) …
  10. Math

    Find the shortcut. Solve these problems. Then find and explain a shortcut method for finding the answer. 52(Squared) - 42 (squared) = 82 (Squared) - 72 (Squared) = 122 (Squared) - 112 (Squared) = 312 (Squared) - 302 (Squared) = 892 …

More Similar Questions